Family Psychoeducation in Reducing the Occurrence of Depression in Elderly: A Systematic Review - Cece Indriani; Yati Sri Hayati; Titin Andri Wihastuti (International Journal of Science and Society, 2020)
Depression is a chronic prevalence and recurrence disturbance. Depression in the elderly characterized by sadness, low interested in doing activity, and inability to feel happiness. But most families ignore it because they think it is a common problem in the elderly. Family psychoeducation therapy is one of the elements of family mental health care programs by providing information, education through therapeutic communication to reduce the scale of depression in the elderly. This systematic review aimed to determine family psychoeducation in reducing the occurrence of depression in the elderly.This systematic review begins with a question in advance and specify the destination, then search for the exact keyword searching to identify the data required in accordance with the purpose of the method of "AND" and "OR". After getting data from the searching results from 2005 to 2019 using proquest international databases, PubMed, science direct, and then proceed with the selection of DOAJ PRISMA flow diagram and criticism JBI tool to obtain the relevant article 23 to be analyzed into a systematic review. Family psychoeducation can improve cognitive abilities because in therapy contains elements that can improve family knowledge about the disease, teach techniques that can help families to know the symptoms of deviant behavior, as well as increased support for the family members themselves. This therapy can also reduce the scale of depression in the elderly. Family psychoeducation therapy can improve cognitive and psychomotor abilities significantly. Thus it can be used to improve the elderly and families coping itself. This therapy is not only used for people with schizophrenia, but also the patient's psychosocial, including depression in the elderly.